On Determinants of Cooperatives’ Perceived Effectiveness in Terms of Financial and Social Performance - Angelita L. Paradero; Danilo M. Te; Leomarich F. Casinillo (Philippine Social Science Journal, 2022)
Cooperatives are vital in the economy, hence, it is practically important to examine the factors that may influence their performance. This study focused on determining the factors that predict cooperatives' perceived effectiveness in terms of financial and social performance in Eastern Visayas, Philippines. A random sampling technique was employed to gather primary data to 438 respondents composed of the board of directors, managers, officers, and members. For data analysis, Partial Least Square-Structural Equation Modeling (PLS-SEM) was utilized to analyze the Likert scale data based on the survey participants' responses. Results showed that cooperatives' governance, members' participation, and training and development significantly predicted cooperatives' perceived effectiveness in terms of financial and social performance. Hence, management of the cooperatives should develop a culture of effective governance that includes transparency, management accountability, and members' democratic participation; encourage members' economic participation and; conduct periodic training to help the cooperatives attain their social and financial goals.